A prospective observational pharmacovigilance study of adverse drug reaction monitoring in patients of MDR-TB at tertiary care hospital - Baig, Mirza Shiraz; Kale, Monali Raghunath; Lamb, Avinash (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The emergence of drug resistant mycobacteria has become a significant public health problem world over creating an obstacle to effective TB control. ADRs are common in patients of MDR-TB on DOTs-Plus drug regimen. Present study was carried out in tertiary care hospital. Identification of types and frequency of adverse drug reactions in Intensive and continuation phase of MDR-TB Patients. Methods: It was a prospective observational study conducted in Department of TB- Chest and Medicine, Govt. Medical College, Aurangabad, Maharashtra, India. All the MDR-TB patients admitted at the directly observed treatment, short course plus (DOTS plus) Center at Medical College Hospital were enrolled and were monitored for ADRs. The causality and severity of the reactions were determined using Naranjo algorithm and Hartwig questionnaire, respectively. Results: A total of 121 tuberculosis patients of MDR-TB on DOTS therapy were enrolled for the study. Out of 121 patients, 13 were dropouts, 6 died, 7 defaulted so 108 patients assessed for ADRs, 48 patients developed 61 (56.48%) adverse drug reactions. The higher numbers of ADRs were observed in age group 31-40yrs followed by 21-30yrs which were more common in men. Majority of adverse drug reactions were Gastrointestinal (GI) problems 32 (52.45%), followed by Ototoxicity 7 (11.48%) and Psychiatric Manifestations 6 (9.84%) and skin problems 3 (4.92%). On evaluation of the causality of ADRs, majority were found to be Possible (59.02%). The severity assessment showed that most of the patients ADRs were of moderate level (50.82%).Some patients required treatment withdrawal and replacement with other drug and most of the patients were managed with supportive medication without removing anti-tubercular drug from their treatment regimen. Conclusions: ADRs are major factor limiting completion of drug therapy under RNTCP and occurrence of drug resistance which requires attention of all health care professionals.